Increasing of Production and Quality of Cherry Tomato (Solanum lycopersicum var. cerasiforme) through Used of Various Growth Medium Compositions and SP-36 Fertilizer Dosages - Hisworo Ramdani; Arifah Rahayu; Haris Setiawan (JURNAL AGRONIDA, 2018)
This study was aimed at assessing the response of cherry tomato to planting mediacomposition and SP-36 fertilizer rates. A factorial completely randomized design with two factorswas used. The first factor was planting media compositions, namely 100% soil, soil + rice huskcharcoal (1:1), soil + manure (1:1), rice husk charcoal + manure (1:1) and soil + rice huskcharcoal + manure (1:1:1). The second factor was SP-36 fertilizer rates, namely no fertilizer (0%R); 155.5 kg/ha (50% R); 311 kg/ha (100% R) and 466.5 kg/ha (150% R). The recommended rate(R) was 311 kg/ha. Results showed that cherry tomato plants grown in planting medium of soil +manure significantly had higher plant height, number of leaves, number of fruits and total solublesolid content than plants grown in the other planting media. Administration of SP-36 fertilizer indifferent rates was not found to significantly affect the growth, production and fruit quality ofcherry tomatoes. Cherry tomato grown in planting medium of soil + rice husk charcoal + manureand fertilized with recommended rate of SP-36 fertilizer (100% R) produced the highestfruit/plant weight and saleable fruit weight.Keywords: cherry tomato, total soluble solid, saleable fruit, rice husk charcoal, manure